Live Recombinant NDV-Vectored H5 Vaccine Protects Chickens and Domestic Ducks From Lethal Infection of the Highly Pathogenic H5N6 Avian Influenza Virus - Lee, Jiho; Kim, Deok-hwan; Noh, Jinyong; Youk, Sungsu; Jeong, Jei-hyun; Lee, Joong-bok; Park, Seung-Yong; Choi, In-soo; Lee, Sang-Won; Song, Chang-seon (Frontiers in Veterinary Science, 2022)
The H5 subtype highly pathogenic avian influenza virus (HPAIV) has been introduced to South Korea every two or three years via wild migratory waterfowls, causing devastating damages to the poultry industry. Although most damages and economic losses by HPAIV are focused on chicken layers, domestic ducks are known to play a major role in the farm-to-farm transmission. However, most HPAIV vaccine studies on poultry have been performed with oil-emulsion inactivated vaccines. In this study, we developed a live recombinant Newcastle disease virus (NDV)-vectored vaccine against H5 HPAIV (rK148/ES2-HA) using a previously established NDV vaccine strain (K148/08) isolated from a wild mallard duck. The efficacy of the vaccine when administered via the oculonasal route or as a spray was evaluated against lethal H5 HPAIV infection in domestic ducks and chickens. Oculonasal inoculation of the rK148/ES2-HA in chickens and ducks elicited antibody titers against HPAIV as early as 1 or 2 week after the single dose of vaccination, whereas spray vaccination in ducks elicited antibodies against HPAIV after the booster vaccination. The chickens and ducks vaccinated with rK148/ES2-HA showed high survival rates and low viral shedding after H5N6 HPAIV challenge. Collectively, vaccination with rK148/ES2-HA prevented lethal infection and decreased viral shedding in both chickens and ducks. The vaccine developed in this study could be useful in suppressing the viral shedding in H5 HPAIV outbreaks, with the ease of vaccine application and fast onset of immunity.